Political Leaders on the COVID-19 Pandemic: Analysis of the Sejm Discourse - Hartliński, Maciej; Klepański, Jakub (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
Utterances of political leaders participating in a parliamentary debate, especially in crisis situations, are of exceptional significance. The aim of the study is to analyse positions and declarations of political leaders towards the COVID-19 pandemic in Poland as regards politicians’ speeches made in the Sejm. Quantitative and qualitative analyses were performed on 504 speeches made by chairpersons of parties and parliamentary clubs and circles. The analysis showed that the issue of COVID-19, although it was the most important problem for Poles for many months, did not receive as much attention from political leaders in the Sejm. The leaders of opposition groups criticised the government and called for action. In contrast, the leaders of ruling parties’ coalition did not actively participate in the Sejm discourse.

Słowa przywódców politycznych w debacie parlamentarnej, zwłaszcza w sytuacjach kryzysowych, mają szczególne znaczenie. Celem opracowania jest analiza stanowisk i deklaracji przywódców politycznych wobec pandemii COVID-19 w Polsce na przykładzie wystąpień w Sejmie. Analizie ilościowej i jakościowej poddano 504 wystąpienia przewodniczących partii oraz klubów i kół poselskich. Analiza ukazała, że problematyka będąc przez wiele miesięcy najważniejszą kwestią dla Polaków, nie cieszyła się równie wielką uwagą przywódców politycznych w Sejmie. Przywódcy ugrupowań opozycyjnych byli aktywni w krytykowaniu rządu oraz wysuwaniu propozycji działań. Z kolei przywódcy partii rządowych nie brali aktywnego udziału w debacie.
Przywódcy polityczni wobec pandemii COVID-19. Analiza dyskursu w Sejmie
Keywords: political leaders; parliamentary speech; political discourse; COVID-19; przywódcy polityczni; przemówienia parlamentarne; dyskurs polityczny; COVID-19